Optimum Design Using Genetic Algorithm and Discrete-element Method: Application to Vibration Feeder Design for E-waste Recycling Automation - HAYASHI, Naohito; KATAGIRI, Jun; UEDA, Takao; KOYANAKA, Shigeki (Resources Processing, 2023)
This study is an engineering application of an optimum design approach using the discrete element method (DEM) and a genetic algorithm (GA) which is one of the most commonly used evolutionary computation algorithms. The three-dimensional shapes of waste electrical and electronic equipment (WEEE) were directly applied in a DEM simulation. The DEM-GA simulation was applied to design the tray set on a single-item feeder for recycling WEEEs; as a result, we obtained the left-right asymmetrical tray shape. Moreover, unlike conventional symmetrical trays, the asymmetrical shape induced complex side forces to prevent clogging and to untangle any clogs that had formed. We manufactured a zig-zag type asymmetrical tray and examined its feeding performance. Finally, we confirmed that the asymmetrical tray was more effective to prevent the feeding stop when compared to the symmetrical tray.